METHODOLOGY FOR ASSESSING THE CONSEQUENCES OF THE DEVELOPMENT OF ARTIFICIAL INTELLIGENCE AND ITS IMPACT ON THE HUMAN FACTOR - Yazdonova Sakhiba Kurbanovna (Bright Mind Publishing, 2025)
This article examines artificial intelligence, which has emerged as one of the main technological drivers of the 21st century, its role on a global scale, in particular its deep penetration into almost all layers of economic, political, social, and cultural life, and a socio-philosophical analysis of how the large-scale introduction of AI will radically change the forms of human activity, professional labor relations, intellectual potential, and even psychological stability. A methodology for systematically studying the consequences of the development of AI, especially its impact on the human factor, is developed.
Keywords: Artificial intelligence, human factor, technological progress, psychological, sociological, and cognitive diagnostic methods, psychometric indicator.